Mechanisms of recovery from aphasia: evidence from positron emission tomography studies. Issue 2 (1st February 1999) - Warburton, Elizabeth; Price, Cathy J; Swinburn, Kate; Wise, Richard J S
Abstract : OBJECTIVES: Language functions comprise a distributed neural system, largely lateralised to the left cerebral hemisphere. Late recovery from aphasia after a focal lesion, other than by behavioural strategies, has been attributed to one of two changes at a systems level: a laterality shift, with mirror region cortex in the contralateral cortex assuming the function(s) of the damaged region; or a partial lesion effect, with recovery of perilesional tissue to support impaired language functions. Functional neuroimaging with PET allows direct observations of brain functions at systems level. This study used PET to compare regional brain activations in response to a word retrieval task in normal subjects and in aphasic patients who had shown at least some recovery and were able to attempt the task. Emphasis has been placed on single subject analysis of the results as there is no reason to assume that the mechanisms of recovery are necessarily uniform among aphasic patients. METHODS: Six right handed aphasic patients, each with a left cerebral hemispheric lesion (five strokes and one glioma), were studied. Criteria for inclusion were symptomatic or formal test evidence of at least some recovery and an ability to attempt word retrieval in response to heard word cues. Each patient underwent 12 PET scans using oxygen-15 labelled water (H2 15 O) as tracer to index regional cerebral blood flow (rCBF). The task, repeated six times, required the patient to think of verbs appropriate to different lists of heard noun cues. The six scans obtained during word retrieval were contrasted with six made while the subject was "at rest". The patients' individual results were compared with those of nine right handed normal volunteers undergoing the same activation study. The data were analysed using statistical parametric mapping (SPM96, Wellcome Department of Cognitive Neurology, London, UK). RESULTS: Perception of the noun cues would be expected to result in bilateral dorsolateral temporal cortical activations, but as the rate of presentation was only four per minute the auditory perceptual activations were not evident in all people. Anterior cingulate, medial premotor (supplementary speech area) and dorsolateral frontal activations were evident in all normal subjects and patients. There were limited right dorsolateral frontal activations in three of the six patients, but a similar pattern was also found in four of the nine normal subjects. In the left inferolateral temporal cortex, activation was found for the normal subjects and five of the six patients, including two of the three subjects with lesions involving the left temporal lobe. The only patient who showed subthreshold activation in the left inferolateral temporal activation had a very high error rate when performing the verb retrieval task. CONCLUSIONS: The normal subjects showed a left lateralised inferolateral temporal activation, reflecting retrieval of words appropriate in meaning to the cue from the semantic system. Lateralisation of frontal activations to the left was only relative, with right prefrontal involvement in half of the normal subjects. Frontal activations are associated with parallel psychological processes involved in word retrieval, including task initiation, short term (working) memory for the cue and responses, and prearticulatory processes (even though no overt articulation was required). There was little evidence of a laterality shift of word retrieval functions to the right temporal lobe after a left hemispheric lesion. In particular, left inferolateral temporal activation was seen in all patients except one, and he proved to be very inefficient at the task. The results provide indirect evidence that even limited salvage of peri-infarct tissue with acute stroke treatments will have an important impact on the rehabilitation of cognitive functions.